Nuoren sairastuminen skitsofreeniseen häiriöön : perheterapeuttinen tarkastelutapa - Pihlajarinne, Marja-Leena (1994)
The aim of the study was to investigate the onset of a schizofrenic disorder at a young age (age range 14-28) in the family context. The problems examined the individuation and separation of the young person, the position of the young person in the family system, the problem of identification, sexual identity and the Oedipal triangle, differences between boys and girls and changes in these areas during a two year follow-up period. The study was carried out as a qualitative case study. Seven patients and families took part in the study. The patients were located through the project concerning New Schizophrenic Patients undertaken by the Mental Health Organisation of Central Finland. Individuation and separation was studied using dynamic psychotherapy and the wholeness of the family by systemic family therapy. Data was collected by means of notes taken during each family therapeutic session. The family therapeutic sessions were also videotaped about every second time. On the basis of the videotapes the descriptions of selected episodes were obtained and from these were formed the variables "dominant speaker" and "distribution of emotional ties in a family". The quantitative data so formed was designeed to support the qualitative analysis. Individuation and separation were also estimated using the forms of the NSP project. Already in the beginning of the study the girls were more active and more capable in their individuation and separation development than the boys. They were also more individualized and separated during the two-years follow-up than the boys. But the boys too showed development during the follow-up in both individuation and separation, as well as in clinical estimation. Both sexes formed an Oedipal triangle with their parents. There were strong conflicts between the parents of the young patients. Two of the girls had taken up the role of therapist in their families and one of them was becoming independent without the necessary support from the parents. The boys were in the middle of their parents' conflicts depressed and tightly bound to the mother. It was concluded that the young adult with schizophrenia had met with longstanding difficulties in identifying with the parent of the same sex, because the relationship was one of great conflict. The development of individuation and separation according to age and the further development of identification were imperfect. The illness began, when the young adult had to take on the responsibilities of a grown-up person while still not ready. In many families the changes aimed at by the theraphy were realized.